The Role of Teachers and Parents in Preventing the Influence of LGBT on Adolescents - Andi Sadriani; Dyan Paramitha Darmayanti; Ibrahim Arifin; M. Ridwan Said Ahmad (Pinisi Journal of Social Science, 2023)
The phenomenon of LGBT that is currently a widely discussed issue in Indonesian society is the increasing promotion or advertisements on social media regarding the LGBT community. This research aims to provide understanding to parents and educators about the impacts and dangers that arise from deviant sexual behavior. The goal is to enable them to provide sexual education, instill religious values and norms, as well as monitor the play environment and social interactions of children as an effort to prevent the negative effects of sexual disorientation and LGBT on children and adolescents. The research method used in this study is literature review, which was conducted to find relevant theoretical references to the existing problem. The focus of this research is on parents and educators in all institutions, especially in the field of education. The research findings indicate several things. First, it is found that issues of sexual deviance tend to arise when children and adolescents are influenced by their surrounding environment. Second, sexual deviance or sexual disorientation occurs due to psychological or mental disorders. Third, there is a lack of sexual education for children and adolescents due to a lack of parental understanding. Fourth, to anticipate LGBT issues among adolescents and children, it is important to strengthen religious approaches in their education.Bottom of FormKeywords: LGBT, The Role of Parents